The Obligation of Sharia Certification For Notaries In The Preparation of Financing Contract Deeds In Islamic Banking - Maulida, Siti Anisa (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This study discusses the urgency and regulation of sharia certification obligations for notaries who make financing agreements in Islamic banking in Indonesia. The main problem arises because there is no legal norm that regulates notary sharia certification, thus creating a legal vacuum (rechtsvacuum) which has an impact on legal uncertainty, low legitimacy of deeds, potential disputes, and the risk of violating sharia principles such as the prohibition of usury, gharar, and maysir. This study formulates two main problems: (1) the urgency of regulating the obligation of notaries to have sharia certificates in making sharia financing agreements, and (2) the design of sharia certification regulations for notaries in order to increase sharia compliance in financing agreements in Islamic banking. The research method used is normative juridical with a statutory, conceptual, and comparative legal approach, based on primary, secondary, and tertiary legal materials. The results of the study indicate that notary sharia certification is very important to ensure the conformity of deeds with sharia principles and positive law. The necessary regulations must include a comprehensive curriculum containing Islamic legal principles, fatwas from the National Sharia Council (DSN-MUI), national regulations, and structured education and competency testing. Furthermore, a regular monitoring and evaluation mechanism by the Sharia Supervisory Board (DPS) is necessary to maintain professional standards and Sharia compliance. Comparison with practices in other countries, particularly Turkey, demonstrates the need for Indonesia to adopt more stringent and systematic regulations. This study recommends the establishment of formal regulations regarding mandatory Sharia notary certification, an integrated certification and supervision body, the implementation of training and competency testing, and optimizing the role of the DPS in overseeing Sharia compliance.